New insights into the role of cytochrome P450 reductase (POR) in microsomal redox biology - Todd D. Porter (Elsevier, 2012)
Cytochrome P450 reductase (POR) is an essential electron transfer protein located on the endoplasmic reticulum of most cell types, and has long been appreciated for its role in cytochrome P450-mediated drug metabolism. Additional roles and electron acceptors for POR have been described, but it is largely with the recent availability of POR-null tissues that these supplemental roles for POR have been able to be explored. These studies have confirmed POR as the principal redox partner for the microsomal P450s responsible for drug and xenobiotic metabolism as well as cholesterol and bile acid synthesis, and for heme oxygenase, which catalyzes the initial step in the breakdown of heme. Surprisingly, these studies have revealed that squalene monooxygenase, an enzyme essential to cholesterol synthesis, has a second unknown redox partner in addition to POR, and that 7-dehydrocholesterol reductase, previously proposed to require POR as an electron donor, functions fully independently of POR. These studies have also helped define the role of cytochrome b5 in P450 catalysis, and raise the question as to the extent to which POR contributes to b5-dependent redox pathways.